ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR KOTA BALIKPAPAN PADA MATERI SATUAN WAKTU TAHUN AJARAN 2015/2016 - Rahayu Sri Waskitoningtyas (Universitas PGRI Madiun, 2016)
This study is meant to describe: a) The difficulty faced by fifth grader of Balikpapan City in learning mathematics especially in learning about “Time Unit”. b). the reasons behind those difficulty faced by the students of fifth grade of Balikpapan City in learning “Time Unit”. the type and approache of the research are descriptive with qualitative approach. The data collection method used in this research are documentation, test, observation and Questionnaire. Based on the final analysis data, the researcher found that the difficulty percentage faced by the students in factual is 14,4%, the difficulty face in conceptual is 56,9%, the difficulty in skills is 42,2% and the difficulty faced by the students in principal is 76,7%. The causes of those difficulty in learning comes from inside and outside of students themselves. It is hoped that teacher can drill students in mastering the concept, skills and principal of “Time Unit” in the hope to reduce the students’ difficulty in mastering the Time Unit material.